Letter (copy) : The Scottish ambulances in Spain - Tewson, Vincent
042-0133-001 HVT/FC/EW/131 Secretary's 13th July, 1937. Sir Daniel Stevenson, Spa Hotel, Buxton, Derbyshire. Dear Sir Daniel, The Scottish Ambulances in Spain. I have your letter of the 3rd July which arrived during Sir Walter's absence from the office. I do not expect him back until Monday next, but I am sure he will desire me to thank you for the information which you have sent. Yours sincerely, Assistant Secretary. 292/946/42/133